IMPLEMENTASI UNDANG-UNDANG NOMOR 21 TAHUN 2019 TENTANG KARANTINA HEWAN, IKAN DAN TUMBUHAN PADA BALAI KARANTINA HEWAN, IKAN DAN TUMBUHAN NTT (STUDI KARANTINA HEWAN) - Narut, Marianus G. P.; Nursalam, Nursalam; Seran, Delila A. Nahak; Mau, Alfred O. Ena (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
Animal quarantine policies are an essential instrument in preventing the spread of animal diseases, safeguarding animal health before distribution, and ensuring food safety and ecosystem security. This study aims to evaluate the implementation of such policies at the Animal, Fish, and Plant Quarantine Center in East Nusa Tenggara. Using a qualitative approach, this research employs a triangulation method that includes observation, interviews, and documentation to obtain in-depth data on the effectiveness of the policy and the challenges encountered in its implementation. The findings of this study indicate that the implementation of animal quarantine policies at the Animal, Fish, and Plant Quarantine Center in East Nusa Tenggara has not been optimal, despite the relevant regulations being in place. One of the main obstacles identified is the lack of effective socialization and communication to the public, especially to quarantine service users, resulting in a low level of understanding regarding the applicable quarantine procedures. This suggests that, while regulations exist, their effectiveness is heavily dependent on public understanding and active participation. Furthermore, limited access to clear and comprehensive information regarding quarantine procedures, as well as a lack of training for involved personnel, also serve as barriers to optimizing the policy's implementation. To enhance the effectiveness of animal quarantine policies, a comprehensive strategy is needed, which includes several key actions, one of which is strengthening socialization through direct engagement with the public, particularly quarantine service users. This aims to improve and deepen their understanding of quarantine procedures, ensuring more effective policy implementation. Additionally, these measures are expected to not only enhance service quality but also improve operational efficiency and monitoring accuracy. Thus, animal quarantine policies are expected to have a broader impact, not only on animal health but also on food safety and the overall well-being of society, which in turn will strengthen animal disease control systems and maintain ecosystem balance.